Penerapan pembelajaran kontekstual dalam Pendidikan Agama Islam - Farel Ridho Pratama; Tommy Raffel; Gusmaneli . (CV. ITTC INDONESIA, 2025)
The teaching of Islamic Religious Education (PAI) is required not only to convey religious knowledge but also to instill values ​​and morals that can be applied in students' daily lives. However, the dominant lecture-based learning method often leaves students passive and lacking a deep understanding of religious values. Therefore, a learning approach is needed that connects learning materials to students' real-life contexts. The Contextual Teaching and Learning (CTL) model is offered as a solution because it emphasizes learning activities involving direct experience, problem-solving, and reflection on the socio-religious conditions surrounding students. This article uses a literature review method by reviewing various research references related to the application of CTL in PAI. The results indicate that CTL can improve students' understanding of religious concepts, learning motivation, religious attitudes, and social skills. Despite its positive impact, CTL implementation still faces challenges such as limited teacher competency and learning support facilities. With the support of teacher professionalism and the provision of a conducive learning environment, CTL can be an effective approach to achieving PAI learning objectives that are more comprehensive and relevant to students' developmental needs.